Method for recycling battery pole powder

CN116487746BActive Publication Date: 2026-10-13GUIZHOU CNGR XINGYANG ENERGY STORAGE TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310065214.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-03
Publication Date
2026-10-13
Estimated Expiration
2043-02-03

AI Technical Summary

Technical Problem

[0007]针对传统电池正极材料回收工艺的金属回收不完全、金属回收率较低等问题中的至少一部分,本发明提供了一种电池极粉的回收方法

Benefits of technology

[0026]1、根据箔材例如铝箔的延展性及其在破碎和强化筛分中的变化,选择控制破碎后电极材料尺寸在2-3cm,减少了破碎时细铝粒产生,降低了电极粉因细铝粒包覆的损失,减少了电极粉体中铝含量;避免了因尺寸大而在筛分时卷曲,导致电极粉体残留的问题;有效增强了除氟过程对铝箔和电极粉体分离的促进作用;降低了电极粉体中铝含量和后续除铝成本,提高了回收的电极粉体品位和粉体回收率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a battery pole powder recycling method and belongs to the technical field of waste battery recycling and utilization. The battery pole powder recycling method comprises the following steps: crushing battery electrode materials, soaking the battery electrode materials in a weak alkaline solution, draining the weak alkaline solution, roasting, and screening to obtain electrode powder and foil. The battery pole powder recycling method solves the problems of electrode powder and foil stripping and fluorine removal, improves the stripping efficiency and the grade of the powder, reduces the content of impurities such as aluminum and fluorine in the positive electrode powder, and effectively improves the recovery rate of the pole powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waste battery recycling technology, and in particular to a method for recycling battery electrode powder. Background Technology

[0002] In the recycling process of spent lithium batteries, it is necessary to separate the active material from the current collector and remove fluoride to obtain powder materials suitable for the subsequent recycling of cobalt, nickel, manganese, and lithium. In the pretreatment process of lithium iron phosphate batteries, the traditional powder stripping method uses 3-5 stages of crushing to ultimately break the electrode sheets into particles smaller than 1mm. Combined with 3-4 rounds of sieving and air classification, approximately 96%-98% of the powder is recovered. However, the powder produced by this method contains 3%-5% ultrafine aluminum particles, which mix into the sieved powder, affecting the powder grade. Furthermore, the recovered aluminum particles may clump together, encapsulating black powder within them, which also impacts the powder yield. Meanwhile, when the aforementioned raw materials enter the leaching process, they are prone to overflowing and hydrogen production, causing certain problems and risks to production. Furthermore, since the binders and electrolytes in lithium iron phosphate batteries are fluorine-containing compounds, approximately 10% of the fluoride escapes during pretreatment. The remaining fluorides enter the leaching section with the powder. Although some fluorine-containing compounds can be removed in the leaching section, a certain amount of fluoride still enters subsequent extraction and other processes. Fluorides not only cause corrosion of production equipment but also affect the quality of products such as nickel, cobalt, and lithium. If some of the fluoride can be removed during the battery pretreatment stage, the difficulty of hydrometallurgy and the cost of fluoride removal can be greatly reduced, and the recovery rate of valuable metals can be improved.

[0003] Therefore, in the pretreatment stage of lithium iron phosphate battery recycling, powder stripping and fluoride removal are key challenges that need to be addressed. Currently, commonly used methods for powder stripping and defluorination include: 1) disassembling the battery to obtain positive electrode sheets, then performing multi-stage crushing, sorting, and sieving to obtain powder material; 2) calcining the battery materials followed by multi-stage crushing and sieving to obtain powder; and 3) soaking the electrode sheets in an alkaline solution to dissolve the aluminum foil completely using the alkaline solubility of aluminum, then filtering and drying to obtain powder material. These three methods have the following drawbacks:

[0004] (1) Multi-stage crushing and sorting: The electrode sheets after dismantling waste lithium iron phosphate batteries need to be crushed in 3-5 stages. During the repeated crushing and screening of the electrode sheets, the crushed aluminum is easily kneaded into spherical shape, which encapsulates a large amount of powder material, resulting in a reduction in powder yield.

[0005] (2) The size of the crushed material is too small: Multi-stage crushing produces a large amount of fine aluminum powder. Simple mechanical screening cannot completely separate the powder from the aluminum particles, and the aluminum content in the powder is still high. It is necessary to add an aluminum removal process in the subsequent processing. At the same time, even if the fine aluminum particles in the powder are treated at high temperatures above 400-550℃ to break the adhesiveness of the binder, it is difficult to completely separate the powder from the aluminum foil because the powder is wrapped in the aluminum particles.

[0006] (3) Chemical stripping method is costly: After dismantling waste batteries, the aluminum foil is dissolved using alkaline substances such as liquid alkali to obtain clean powder material. The disadvantage of this method is that it consumes a large amount of alkaline substances, which increases the production cost. In addition, the process generates hydrogen gas and a large amount of heat due to the aluminothermic reaction, which poses certain safety hazards. Summary of the Invention

[0007] To address at least some of the problems in traditional battery cathode material recycling processes, such as incomplete metal recovery and low metal recovery rates, this invention provides a method for recycling battery electrode powder.

[0008] According to one aspect of the present invention, a method for recycling battery electrode powder is provided, comprising the following steps: crushing the battery electrode material, soaking it in a weakly alkaline solution and draining it, and then calcining and sieving it to obtain electrode powder and foil.

[0009] In the above-mentioned technical solution of the present invention, during the process of separating battery electrode materials into electrode powder and foil, the battery electrode materials are first crushed, and the crushed battery electrode materials are soaked in a weakly alkaline solution. This can deeply remove free fluoride ions, thereby improving the fluoride removal rate and effect, preventing fluoride from adhering to the electrode powder and affecting the quality of the electrode powder product. It can also avoid the problem of fluoride corrosion of equipment during subsequent processing of electrode powder, and reduce the cost of defluorination. Furthermore, the slight solubility of aluminum in the weakly alkaline solution creates tiny cracks between the aluminum foil and the electrode powder, which can promote the peeling of the powder and aluminum foil. After calcination and sieving, the recovery rate of valuable metals in the electrode powder can be improved, which is especially suitable for the resource recycling of waste lithium iron phosphate batteries and ternary lithium batteries.

[0010] In a further preferred embodiment, the size of the broken battery electrode material is 2-3 cm. Here, the size of the broken battery electrode material refers to the length of a single rectangular sheet formed after breakage, or the distance between the two furthest points on the outer surface of a single irregularly shaped material.

[0011] In this solution, when using a shear crusher to crush the electrode sheets, only 1-2 crushing operations are generally required to obtain loose electrode sheets with a size of 2-3 cm. Because aluminum foil has good ductility, if the aluminum foil size is too small during crushing, more crushing operations are needed, which easily produces fine aluminum particles and causes agglomeration, and also easily leads to the aluminum foil coating the electrode powder. If the aluminum foil size is too large, fewer crushing operations are needed, but it is prone to curling during vibratory sieving, making it difficult to separate the aluminum foil from the powder. This solution controls the size of the crushed material within the 2-3 cm range, which reduces the generation of fine aluminum particles, avoids aluminum foil curling during subsequent sorting, and achieves efficient separation of electrode powder and aluminum foil. Furthermore, less positive electrode active material remains on the aluminum foil, allowing for direct packaging and use.

[0012] In a further preferred embodiment, the mass ratio of electrode material to weakly alkaline solution during the soaking process is 2:1-10:1, the soaking temperature is 50℃-95℃, and the soaking time is 60-90 minutes. Under the soaking conditions of this embodiment, the recovery rate of the obtained electrode powder and the fluoride removal rate can be improved.

[0013] In a further preferred embodiment, the weakly alkaline solution is a carbonate solution.

[0014] In this scheme, carbonate is used as the soaking solution. On the one hand, carbonate acts as a defluorination additive, utilizing its weak alkalinity to neutralize hydrofluoric acid, thereby improving the fluoride removal rate. On the other hand, carbonate's slight solubility in aluminum is utilized. After the positive electrode is soaked in carbonate, the aluminum foil surface slightly dissolves, creating tiny cracks between the aluminum foil and the electrode powder. During the calcination stage, the carbonate is heated at high temperatures to produce carbon dioxide gas. The large amount of gas produced in a short time causes further stress expansion in the existing cracks. In addition, during the high-temperature calcination pyrolysis process, the binder, such as polyvinylidene fluoride (PVDF), is carbonized. Since the bonding force of PVDF is mainly the intermolecular hydrogen bonds and intermolecular van der Waals forces, these forces are destroyed under high temperature during the pyrolysis process. Therefore, the electrode active material can easily detach from the foil, thereby accelerating the separation of the positive electrode powder from the foil.

[0015] In a further preferred embodiment, the weakly alkaline solution is one or more of sodium bicarbonate, ammonium bicarbonate, sodium carbonate, potassium bicarbonate, and potassium carbonate. Soaking the electrode material in the aforementioned weakly alkaline solution is beneficial for separating the positive electrode powder from the foil.

[0016] In a further preferred embodiment, the weakly alkaline solution is a saturated or supersaturated solution. Using a saturated or supersaturated solution can increase the reaction rate between the weakly alkaline solution and the foil, allowing for a more complete reaction and thus improving the recovery rate of the electrode powder.

[0017] In a further preferred embodiment, the mass concentration of sodium bicarbonate is 5%-15%; the mass concentration of potassium carbonate is 45%-55%; and the mass concentrations of sodium carbonate, potassium bicarbonate, and ammonium bicarbonate are 15%-30%. Using a weakly alkaline solution not only dissolves the foil material, yielding clean electrode powder, but also reduces production costs, making it suitable for large-scale applications.

[0018] In a further preferred embodiment, the calcination temperature is 450℃-550℃, and the calcination time is 2h-4h. Under the calcination conditions of this embodiment, the recovery rate of the obtained electrode powder and the fluoride removal rate can be further improved.

[0019] In a further preferred embodiment, an auxiliary medium is added during the sieving process to enhance the sieving, and the sieving yields oversize and undersize. The oversize includes the foil and the auxiliary medium, and the undersize includes electrode powder. Preferably, the sieved oversize is subjected to air separation, utilizing the difference in suspension velocity between the auxiliary medium and the foil to blow up the foil, thereby achieving the separation of the auxiliary medium and the foil. Preferably, a circular drum screener is used for sieving.

[0020] The screening method in this scheme achieves two effects: firstly, the flaky materials generate friction with each other as the circular drum screen rotates, causing the electrode powder to detach from the aluminum foil; secondly, the auxiliary medium and the flaky materials, under the combined action of gravity and centrifugal force, improve the separation efficiency of the electrode powder from the aluminum foil, thus greatly improving the electrode powder recovery rate.

[0021] In a further preferred embodiment, the screening specifically includes: transferring the calcined material to a circular drum screen, the circular drum screen being inclined at a 10-30 degree angle to the ground, and adding an auxiliary medium to the circular drum screen for screening. Adding an auxiliary medium, such as zirconium beads, to the circular drum screen utilizes the combined effects of the centrifugal force of the circular drum screen, the gravity vibration of the zirconium beads, and the friction between the sheet aluminum foil and the circular drum screen to improve the separation efficiency of the cathode powder and the aluminum foil, and to increase the powder recovery rate.

[0022] In a further preferred embodiment, the mass ratio of the auxiliary medium to the calcined material is 3:1-1.5:1, the sieving time is 15-25 minutes, the particle size of the undersize material is less than 0.23 mm, the auxiliary medium is one or more of zirconium beads, steel beads, and rubber beads, and the sieve mesh size is 50-80 mesh. This further improves the separation efficiency of the electrode powder from the aluminum foil and further increases the electrode powder recovery rate.

[0023] In a further preferred embodiment, the battery electrode material is a lithium-ion battery cathode material.

[0024] This solution allows for the recycling of lithium-ion battery cathode materials, separating the cathode powder from the aluminum foil. This improves the recovery rate of the cathode powder and enables the reuse of the recycled aluminum foil, achieving full recycling of lithium battery cathode materials. It is particularly suitable for the resource-based recycling of waste lithium iron phosphate batteries and ternary lithium batteries.

[0025] In summary, the battery electrode powder recovery method provided by this invention has at least the following beneficial effects:

[0026] 1. Based on the ductility of foil materials, such as aluminum foil, and its changes during crushing and enhanced screening, the size of the electrode material after crushing is controlled to be 2-3 cm. This reduces the generation of fine aluminum particles during crushing, decreases the loss of electrode powder due to the coating of fine aluminum particles, and reduces the aluminum content in the electrode powder. It also avoids the problem of electrode powder residue caused by curling during screening due to large size. It effectively enhances the promoting effect of the defluorination process on the separation of aluminum foil and electrode powder. It reduces the aluminum content in the electrode powder and the subsequent aluminum removal cost, and improves the grade and recovery rate of the recovered electrode powder.

[0027] 2. Soaking in a weakly alkaline solution serves two purposes. First, it acts as a defluorination additive, neutralizing hydrofluoric acid to effectively and deeply remove free fluoride ions. Second, the slight solubility of aluminum in the weakly alkaline solution creates fine cracks between the aluminum foil and the electrode powder. Furthermore, the carbon dioxide gas produced during calcination promotes the separation of the powder and aluminum foil, allowing for larger crushing sizes, reducing the generation of aluminum powder / particles, and preventing aluminum foil agglomeration that coats the electrode powder. This simplifies the crushing and screening operation, improves the separation effect and efficiency, powder grade, and powder recovery rate.

[0028] 3. By adding an auxiliary medium to the circular drum screen, the centrifugal force of the drum screen, the gravity vibration of the auxiliary medium, and the friction between the sheet aluminum foil and the drum screen work together to improve the separation efficiency of electrode powder and aluminum foil and increase the powder recovery rate. Detailed Implementation

[0029] It should be understood that the specific embodiments given herein are for the purpose of explaining to those skilled in the art and are exemplary only, not restrictive.

[0030] In the following description, numerous specific details are set forth to provide a thorough understanding of the invention. However, it will be apparent to those skilled in the art that the specific details are not required to practice the invention. In other instances, well-known steps or operations have not been described in detail to avoid obscuring the invention.

[0031] The battery electrode powder recycling method provided in this invention includes the following steps: disassembling and recycling a lithium-ion battery to obtain a positive electrode sheet and a negative electrode sheet inside the battery, wherein the positive electrode sheet of the lithium-ion battery is a lithium-containing positive electrode material and the negative electrode sheet is a graphite-containing negative electrode material, such as lithium iron phosphate batteries, ternary lithium batteries, lithium cobalt oxide batteries, lithium manganese oxide batteries, etc.; after crushing the positive electrode sheet, soaking it in a weakly alkaline solution and draining it, then calcining and sieving it to obtain electrode powder and foil.

[0032] In some optional embodiments, the size of the broken battery electrode material is 2-3 cm. For example, the size of the broken battery electrode material can be any value between 2 cm, 2.1 cm, 2.2 cm, 2.3 cm, 2.4 cm, 2.5 cm, 2.6 cm, 2.7 cm, 2.8 cm, 2.9 cm, 3 cm, or 2-3 cm, which helps to reduce the generation of aluminum powder.

[0033] In some optional embodiments, the mass ratio of electrode material to weakly alkaline solution during the soaking process is 2:1-10:1, the solution temperature during the soaking process is 50℃-95℃, and the soaking time is 60-90min.

[0034] For example, the mass ratio of electrode material to weakly alkaline solution during the soaking process can be any value between 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or 2:1-10:1; the solution temperature during the soaking process can be any value between 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, or 50℃-95℃; and the soaking time can be any value between 60min, 65min, 70min, 75min, 80min, 85min, 90min, or 60-90min.

[0035] In some optional embodiments, the weakly alkaline solution is a carbonate solution.

[0036] In some optional embodiments, the weakly alkaline solution is one or more of sodium bicarbonate, ammonium bicarbonate, sodium carbonate, potassium bicarbonate, and potassium carbonate. For example, the weakly alkaline solution can be a sodium carbonate solution or a mixed solution of sodium carbonate and sodium bicarbonate.

[0037] In some alternative embodiments, the weakly alkaline solution is a saturated or supersaturated solution. For example, the weakly alkaline solution may be a saturated sodium carbonate solution or a saturated sodium bicarbonate solution.

[0038] In some optional embodiments, the mass concentration of sodium bicarbonate is 5%-15%, the mass concentration of potassium carbonate is 45%-55%, and the mass concentrations of sodium carbonate, potassium bicarbonate, and ammonium bicarbonate are 15%-30%.

[0039] For example, the mass concentration of sodium bicarbonate solution can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or any value between 5% and 15%; the mass concentration of potassium carbonate can be any value between 45%, 47%, 49%, 51%, 53%, 55%; and the mass concentrations of sodium carbonate, potassium bicarbonate, and ammonium bicarbonate can be any value between 15%, 18%, 21%, 24%, 27%, and 30%.

[0040] In some optional embodiments, the soaked material is drained and transferred to an aerobic or anaerobic environment for roasting at a temperature of 450℃-550℃ for a time of 2h-4h. For example, the roasting temperature can be any value between 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, or 450℃-550℃; the roasting time can be any value between 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h, 4h, or 2h-4h.

[0041] In some optional embodiments, an auxiliary medium is added during the sieving process to enhance the sieving, resulting in oversize and undersize materials; the oversize material includes foil and the auxiliary medium, and the undersize material includes electrode powder. For example, zirconium beads can be selected as the auxiliary tool to enhance the sieving.

[0042] In some optional embodiments, the sieved material is air-separated to separate the auxiliary medium from the foil.

[0043] In some optional embodiments, the screening specifically includes: transferring the roasted material to a circular drum screen, the circular drum screen being inclined at an angle of 10-30 degrees to the ground, and adding auxiliary media to the circular drum screen for screening.

[0044] For example, the roasted material is fed into the internal circular screen of the circular drum screen from the top. At the same time, auxiliary media is added to the circular drum screen for enhanced screening. This scheme makes full use of the centrifugal force generated by the rotation of the circular drum screen, the friction between the material and the circular drum screen, and the vibration force between the auxiliary media and the material. Through the interaction of the above three forces, aluminum foil and powder can be separated well, and the aluminum foil obtained will not curl, which greatly improves the powder recovery rate.

[0045] During the rotation of the cylindrical drum, the powder is discharged from the circular screen into the ton bag from top to bottom, that is, the undersize material is the positive electrode powder, and the sheet aluminum foil and auxiliary medium are discharged from the bottom of the separation drum into the air classifier, that is, the oversize material is the sheet aluminum foil and auxiliary medium, thus realizing the separation of positive electrode powder and foil.

[0046] Preferably, the airflow of the air separator is strong enough to blow up the sheet-like foil to separate the auxiliary medium from the foil. The blown-up aluminum foil will be collected through pipelines.

[0047] In some optional embodiments, the mass ratio of the auxiliary medium to the calcined material, i.e. the material to be screened, is 3:1-1.5:1, the screening time is 15-25 min, the particle size of the undersize material is less than 0.23 mm, accounting for about 98.5%, the aluminum content in the powder is less than 1%, the auxiliary medium is one or more of zirconium beads, steel beads, and rubber beads, and the mesh number of the screening screen is 50-80 mesh. For example, the mass ratio of the auxiliary medium to the calcined material can be any value between 3:1, 2.8:1, 2.5:1, 2.2:1, 2:1, 1.8:1, 1.6:1, 1.5:1, or 3:1-1.5:1; the sieving time can be any value between 15 min, 16 min, 18 min, 20 min, 22 min, 24 min, 25 min, or 15-25 min; and the sieve mesh size can be any value between 50 mesh, 55 mesh, 60 mesh, 65 mesh, 70 mesh, 75 mesh, and 80 mesh.

[0048] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. However, the specific embodiments described are only used to explain this invention and are not intended to limit this invention.

[0049] Example 1

[0050] The battery electrode powder recycling method in this embodiment includes the following steps:

[0051] Disassembling a ternary lithium-ion battery after saltwater discharge yields the battery's positive and negative electrode plates.

[0052] The positive electrode sheet was crushed into loose flakes with a size of 2.5 cm using a shear crusher;

[0053] In particular, only 1-2 crushing operations are needed to obtain a loose positive electrode sheet of 2.5cm;

[0054] The broken sheet electrodes were immersed in a stainless steel cleaning tank. Saturated Na2CO3 weak alkaline solution (16.7% mass concentration) was added at a mass ratio of 4:1 between the broken material and the weak alkaline solution. The tank was stirred and soaked for 80 minutes, and the temperature inside the tank was maintained at 80℃.

[0055] After soaking, the electrode sheet is drained for 30 minutes. After draining, the material is transferred to an aerobic environment at 500℃ and roasted for 2 hours. Under the aerobic high-temperature roasting, the organic binder of the electrode sheet will decompose, thereby greatly reducing the interaction force between the positive electrode active material and the current collector.

[0056] The roasted material is transferred to a circular drum screen for sieving. The screen mesh is 65 mesh. The circular drum screen device is inclined at a 25-degree angle to the ground. At the same time, a certain amount of zircon beads are added at a mass ratio of 2:1 to the input material. The zircon beads have a diameter of 20 mm. The sieving time is 20 min. The particle size of the material passing through the screen is less than 0.23 mm.

[0057] After sieving, the material on the sieve is mainly de-powdered sheet aluminum foil. With the help of airflow separation, the foil and zirconium beads are separated, and the material under the sieve is positive electrode powder.

[0058] After testing, the ternary cathode sheet, after being treated by the above method, showed that the black powder recovery rate (the percentage of recovered black powder mass to the total black powder mass contained in the cathode sheet) was 99.5%, the aluminum content in the black powder was 0.7161%, the residual water-soluble fluoride content in the material was 0.06%, and the fluoride removal rate was 93.4%.

[0059] Example 2

[0060] The battery electrode powder recycling method in this embodiment includes the following steps:

[0061] Disassembling a ternary lithium-ion battery after physical discharge yields the battery's positive and negative electrode plates.

[0062] The positive electrode sheet was crushed into loose flakes with a size of 2cm using a shear crusher;

[0063] In particular, only 1-2 crushing operations are needed to obtain a 2cm loose positive electrode sheet;

[0064] The broken sheet electrode was immersed in a stainless steel cleaning tank. A mixture of 16.7% Na2CO3 and 5% NaHCO3 weak alkaline solution (volume fraction 1:1) was added at a mass ratio of 10:1 between the broken material and the weak alkaline solution. The mixture was stirred and immersed in the cleaning tank for 60 minutes, and the temperature in the tank was maintained at 95℃.

[0065] After soaking, the electrode sheet is drained for 30 minutes. After draining, the material is transferred to an oxygen-free environment at 550℃ for 2 hours. Under the oxygen-free high-temperature calcination, the organic binder polymer compound is decomposed into small molecule compound, which destroys the adhesion between the positive electrode active material and the current collector.

[0066] The roasted material is transferred to a circular drum screen for sieving. The screen mesh is 65 mesh. The circular drum screen device is inclined at a 10-degree angle to the ground. At the same time, a certain amount of zircon beads with a diameter of 20 mm are added according to the mass ratio of zircon beads to the input material of 1.5:1. The sieving time is 15 minutes, and the particle size of the material under the screen is less than 0.23 mm.

[0067] After sieving, the material on the sieve is mainly de-powdered sheet aluminum foil. With the help of airflow separation, the foil and zirconium beads are separated, and the material under the sieve is positive electrode powder.

[0068] After testing, the ternary cathode sheet, after being treated by the above method, showed a black powder recovery rate of 98.5%, an aluminum content of 0.28% in the black powder, a residual water-soluble fluoride content of 0.08%, and a fluoride removal rate of 95.2%.

[0069] Example 3

[0070] The battery electrode powder recycling method in this embodiment includes the following steps:

[0071] Disassembling a ternary lithium-ion battery after saltwater discharge yields the battery's positive and negative electrode plates.

[0072] The positive electrode sheet was crushed into loose flakes with a size of 3cm using a shear crusher;

[0073] In particular, only 1-2 crushing operations are needed to obtain a 3cm loose positive electrode sheet;

[0074] The broken sheet electrodes were immersed in a stainless steel cleaning tank. A saturated sodium bicarbonate solution (8.8% mass concentration) was added at a mass ratio of 2:1 between the broken material and the weak alkali solution. The solution was stirred and soaked in the cleaning tank for 90 minutes, and the temperature in the tank was maintained at 50°C.

[0075] After soaking, the electrode sheet is drained for 30 minutes. After draining, the material is transferred to an aerobic environment at 450℃ and roasted for 2 hours. Under the aerobic high-temperature roasting, the organic binder of the electrode sheet will decompose, thereby greatly reducing the interaction force between the positive electrode active material and the current collector.

[0076] The roasted material is transferred to a circular drum screen for screening. The screen mesh is 80 mesh. The circular drum screen device is inclined at a 30-degree angle to the ground. At the same time, a certain amount of zirconium beads with a diameter of 20 mm are added according to the mass ratio of steel balls to input material of 3:1. The screening time is 20 minutes, and the particle size of the material under the screen is less than 0.23 mm.

[0077] After sieving, the material on the sieve is mainly de-powdered sheet aluminum foil. With the help of airflow separation, the foil is separated from the steel balls, and the material under the sieve is positive electrode powder.

[0078] After testing, the ternary cathode sheet, after being treated by the above method, showed a black powder recovery rate of 99.4%, an aluminum content of 0.1713% in the black powder, a residual water-soluble fluoride content of 0.07%, and a fluoride removal rate of 94.1%.

[0079] Example 4

[0080] The battery electrode powder recycling method in this embodiment includes the following steps:

[0081] Disassembling a lithium iron phosphate battery after physical discharge yields the positive and negative electrode plates.

[0082] The positive electrode sheet was crushed into loose flakes with a size of 2cm using a shear crusher;

[0083] In particular, only 1-2 crushing operations are needed to obtain a 2cm loose positive electrode sheet;

[0084] The broken sheet electrode was immersed in a stainless steel cleaning tank. A mixture of 30% Na2CO3 and 15% NaHCO3 weak alkaline solution (volume fraction 1:1) was added according to the mass ratio of broken material to weak alkaline solution of 10:1. The mixture was stirred and immersed in the cleaning tank for 60 minutes, and the temperature in the tank was maintained at 95℃.

[0085] After soaking, the electrode sheet is drained for 30 minutes. After draining, the material is transferred to an oxygen-free environment at 550℃ for 2 hours. Under the oxygen-free high-temperature calcination, the organic binder polymer compound is decomposed into small molecule compound, which destroys the adhesion between the positive electrode active material and the current collector.

[0086] The roasted material is transferred to a circular drum screen for screening. The screen mesh is 50 mesh. The circular drum screen device is inclined at a 30-degree angle to the ground. At the same time, a certain amount of auxiliary medium (steel balls, rubber balls) is added according to the mass ratio of auxiliary medium (steel balls, rubber balls) to the input material of 1.5:1. The diameter of the auxiliary medium is 20 mm. The screening time is 15 min. The particle size of the material under the screen is less than 0.23 mm.

[0087] After sieving, the material on the sieve is mainly de-powdered sheet aluminum foil. With the help of airflow separation, the foil and zirconium beads are separated, and the material under the sieve is positive electrode powder.

[0088] After testing, the lithium iron phosphate cathode sheet, after being treated by the above method, showed a black powder recovery rate of 97.5%, an aluminum content of 0.08% in the black powder, a residual water-soluble fluoride content of 0.09%, and a fluoride removal rate of 93.2%.

[0089] Comparative Example 1

[0090] This comparative example provides a method for recycling battery electrode powder. Unlike Example 1, in this comparative example, the positive electrode sheet is broken into loose flakes with a size of 8 cm. Specifically, it includes the following steps:

[0091] Disassembling a ternary lithium-ion battery after saltwater discharge yields the battery's positive and negative electrode plates.

[0092] The positive electrode sheet was crushed into loose flakes of 8cm using a shear crusher;

[0093] The broken sheet electrode was immersed in a stainless steel cleaning tank. A 16.7% Na2CO3 weak alkaline solution was added at a mass ratio of 4:1 between the broken material and the weak alkaline solution. The solution was stirred and soaked in the cleaning tank for 80 minutes, and the temperature in the tank was maintained at 80℃.

[0094] After soaking, the electrode sheet is drained for 30 minutes. After draining, the material is transferred to an aerobic environment at 500℃ and roasted for 2 hours. Under the aerobic high-temperature roasting, the organic binder of the electrode sheet will decompose, thereby greatly reducing the interaction force between the positive electrode active material and the current collector.

[0095] The roasted material is transferred to a circular drum screen for sieving. The screen mesh is 65 mesh. The circular drum screen device is inclined at a 25-degree angle to the ground. At the same time, a certain amount of zircon beads are added according to the mass ratio of zircon beads to the input material of 2:1. The diameter of the zircon beads is 20 mm. The sieving time is 20 min. The particle size of the material under the screen is less than 0.23 mm.

[0096] After sieving, the material on the sieve is mainly de-powdered sheet aluminum foil. With the help of airflow separation, the foil and zirconium beads are separated, and the material under the sieve is positive electrode powder.

[0097] After testing, the ternary cathode sheet, after being treated by the above method, showed that the black powder recovery rate was 89.04%, the aluminum content in the black powder was 0.518%, the residual water-soluble fluoride content in the material was 0.12%, and the fluoride removal rate was 92.93%.

[0098] Comparative Example 2

[0099] This comparative example provides a method for recycling battery electrode powder. Unlike Example 1, in this comparative example, the positive electrode sheet is broken into loose flakes with a size of 0.5 cm. Specifically, it includes the following steps:

[0100] Disassembling a ternary lithium-ion battery after saltwater discharge yields the battery's positive and negative electrode plates.

[0101] The positive electrode sheet was crushed into loose flakes of 0.5 cm using a shear crusher;

[0102] The broken sheet electrode was immersed in a stainless steel cleaning tank. A 16.7% Na2CO3 weak alkaline solution was added at a mass ratio of 4:1 between the broken material and the weak alkaline solution. The solution was stirred and soaked in the cleaning tank for 80 minutes, and the temperature in the tank was maintained at 80℃.

[0103] After soaking, the electrode sheet is drained for 30 minutes. After draining, the material is transferred to an aerobic environment at 500℃ and roasted for 2 hours. Under the aerobic high-temperature roasting, the organic binder of the electrode sheet will decompose, thereby greatly reducing the interaction force between the positive electrode active material and the current collector.

[0104] The roasted material is transferred to a circular drum screen for sieving. The screen mesh is 65 mesh. The circular drum screen device is inclined at a 25-degree angle to the ground. At the same time, a certain amount of zircon beads are added according to the mass ratio of zircon beads to the input material of 2:1. The diameter of the zircon beads is 20 mm. The sieving time is 20 min. The particle size of the material under the screen is less than 0.23 mm.

[0105] After sieving, the material on the sieve is mainly de-powdered sheet aluminum foil. With the help of airflow separation, the foil and zirconium beads are separated, and the material under the sieve is positive electrode powder.

[0106] After testing, the ternary cathode sheet, after being treated by the above method, showed a black powder recovery rate of 91.92%, an aluminum content of 0.739% in the black powder, a residual water-soluble fluoride content of 0.11%, and a fluoride removal rate of 92.23%.

[0107] Comparative Example 3

[0108] This comparative example provides a method for recovering battery electrode powder. Unlike Example 2, this comparative example uses an atomized spraying method for defluorination. Specifically, it includes the following steps:

[0109] Disassembling a ternary lithium-ion battery after physical discharge yields the battery's positive and negative electrode plates.

[0110] The positive electrode sheet was crushed into loose flakes with a size of 2cm using a shear crusher;

[0111] During crushing, a mixture of 16.7% Na2CO3 and 5% NaHCO3 weak alkaline solution (volume fraction 1:1) is sprayed through atomization to absorb the hydrogen fluoride produced by the decomposition of the electrolyte.

[0112] The crushed electrode sheets were drained for 30 minutes. After draining, the material was transferred to an oxygen-free environment at 550°C and calcined for 2 hours. Under the oxygen-free high-temperature calcination, the organic binder polymer compound was decomposed into small molecule compound, which destroyed the adhesion between the positive electrode active material and the current collector.

[0113] The roasted material is transferred to a circular drum screen for sieving. The screen mesh is 65 mesh. The circular drum screen device is inclined at a 10-degree angle to the ground. At the same time, a certain amount of zircon beads with a diameter of 20 mm are added according to the mass ratio of zircon beads to the input material of 1.5:1. The sieving time is 15 minutes, and the particle size of the material under the screen is less than 0.23 mm.

[0114] After sieving, the material on the sieve is mainly sheet aluminum foil after powder removal. With the help of airflow separation, the foil and zirconium beads are separated. The material under the sieve is black powder, which is the positive electrode powder.

[0115] After testing, the residual water-soluble fluoride content of the ternary cathode sheet after treatment by the above method was 0.43%, and the fluoride removal rate was 54.7%.

[0116] Table 1. Yield and grade of treated black powder in the examples and comparative examples.

[0117]

[0118]

[0119] As shown in Table 1, the black powder recovery rate in the embodiments all reached over 97%, which is significantly higher than the black powder recovery rate in the comparative example. Furthermore, when calculated using Ni, Co, Mn, and Li, the recovery rates in the embodiments were all higher than those in the comparative example. This demonstrates that the battery electrode powder recovery method of the embodiments of the present invention can significantly improve the recovery rate of positive electrode materials.

[0120] Comparing Comparative Examples 1 and 2 with Example 1, in Comparative Example 1, the positive electrode sheet was broken into loose flakes of 8 cm, and the removal rate of water-soluble fluoride was 92.93%. In Comparative Example 2, the positive electrode sheet was broken into loose flakes of 0.5 cm, and the removal rate of water-soluble fluoride was 92.23%. In Example 1, the positive electrode sheet was broken into loose flakes of 2-3 cm, and the removal rate of water-soluble fluoride was 93.4%. Clearly, positive electrode sheet sizes that are too large or too small are not conducive to the removal of water-soluble fluoride. The battery electrode powder recovery method described in this invention provides a better removal effect for water-soluble fluoride.

[0121] Furthermore, the powder recovery rate in Comparative Example 1 is lower than that in Comparative Example 2, indicating that a small positive electrode size significantly reduces the powder recovery rate. In contrast, the removal rate of water-soluble fluoride in Comparative Example 1 is greater than that in Comparative Example 2. This shows that only within the positive electrode size range specified in the embodiments of the present invention can the obtained powder recovery rate and water-soluble fluoride removal rate achieve optimal results.

[0122] Table 2 shows the defluorination effect in the examples and comparative examples.

[0123] Example 2 0.08% 95.2% Comparative Example 3 0.43% 54.7%

[0124] As shown in Table 2, the immersion defluorination method used in Example 2 resulted in a significantly lower residual water-soluble fluoride content in the material, and a significantly improved fluoride removal rate. Compared to the atomization defluorination method used in Comparative Example 3, the residual water-soluble fluoride content in the material of Example 2 decreased by 81.4%, and the fluoride removal rate increased by 74%. The comparison demonstrates that the battery electrode powder recovery method described in this invention has a significantly better removal effect on free fluoride ions.

[0125] The battery electrode powder recovery method provided in this invention can solve the problems of separating battery active material from the current collector and removing fluoride. Specifically, a fluoride removal additive is used to remove residual fluoride on the electrode sheet; an enhanced sieving method is used to break the electrode sheet into flakes of 2-3 cm in size; shear crushing of the electrode sheet is used; and soaking, calcination, and enhanced sieving in a mixed solvent are employed to achieve efficient separation of the positive electrode active material from the current collector. This simplifies the crushing and sieving operation, improves the separation efficiency and powder quality, and yields sheet-like aluminum foil. Compared with existing separation processes, this invention can quickly and efficiently separate aluminum foil from powder, simplifying and shortening the process flow. It eliminates the need to crush the positive electrode sheet into particles of about 1 mm, while removing water-soluble fluoride and reducing the content of impurities such as aluminum and fluorine in the positive electrode powder, effectively improving the electrode powder recovery rate.

[0126] The technical features described above can be combined arbitrarily. Although not all possible combinations of these technical features are described, any combination of these technical features should be considered to be covered by this specification, provided that such combination does not contain contradictions.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for recycling battery electrode powder, characterized in that, The method includes the following steps: The battery electrode material is crushed into flakes with a size of 2-3 cm, and then soaked in a weak alkaline solution, which is a carbonate solution, with the mass ratio of electrode material to weak alkaline solution being 2:1-10:1 during the soaking process. After soaking, the material is drained, then calcined and sieved to obtain separated electrode powder and foil. The battery electrode material is a lithium-ion battery cathode material; The weakly alkaline solution is one or more of ammonium bicarbonate, sodium carbonate, potassium bicarbonate, and potassium carbonate solution. The mass concentration of potassium carbonate is 45%-55%. The mass concentrations of sodium carbonate, potassium bicarbonate, and ammonium bicarbonate are 15%-30%.

2. The method for recovering battery electrode powder according to claim 1, characterized in that, The soaking temperature is 50℃-95℃, and the soaking time is 60-90 minutes.

3. The method for recovering battery electrode powder according to claim 1, characterized in that, The weakly alkaline solution is a saturated or supersaturated solution.

4. The method for recovering battery electrode powder according to claim 1, characterized in that, The roasting temperature is 450℃-550℃, and the roasting time is 2h-4h.

5. The method for recovering battery electrode powder according to claim 1, characterized in that, An auxiliary medium is added during the screening process to enhance the screening, and the screening yields oversize and undersize materials. The oversize material includes the foil and the auxiliary medium, and the undersize material includes electrode powder.

6. The method for recovering battery electrode powder according to claim 5, characterized in that, The material remaining on the sieve after screening is then subjected to air separation to separate the auxiliary medium from the foil.

7. The method for recovering battery electrode powder according to claim 5, characterized in that, The screening process specifically includes: transferring the roasted material to a circular drum screen, with the circular drum screen inclined at an angle of 10-30 degrees to the ground, and adding auxiliary media to the circular drum screen for screening.

8. The method for recovering battery electrode powder according to claim 7, characterized in that, The mass ratio of the auxiliary medium to the calcined material is 3:1-1.5:1, the sieving time is 15-25 min, and the particle size of the undersize material is less than 0.23 mm. The auxiliary medium is one or more of zirconium beads, steel beads, and rubber beads; The sieve used for the sieving is 50-80 mesh.

Citation Information

Patent Citations

  • Method for recycling and regenerating waste lithium ion battery electrode materials

    CN105990617A

  • Harmless removal method of electrolyte of waste lithium ion battery

    CN110034351A

  • Recycling method of lithium iron phosphate battery positive plate

    CN112661130A

  • Separation and recovery method for positive electrode material and current collector of waste lithium ion battery

    CN115036603A